Pengenalan Moderasi Beragama melalui Metode Cerita pada Santri Taman Pendidikan Al-Qur’an Nagari Seulayat Ulakan - Agam Muhammad Rizki (I-Com: Indonesian Community Journal, 2024)
Indonesia is a multicultural country that has diversity including various religions, cultures, languages, and ethnicities. Apart from being a wealth of diversity, Indonesia has the potential to give rise to conflict caused by extremism and radicalism. Therefore, it is important to introduce religious moderation to society starting from children. Religious moderation is defined as a stage of understanding and practicing in a balanced and fair manner all religious teachings to avoid extreme behavior. Instilling an attitude of religious moderation in children needs to consider the child's happiness so that the goal of instilling religious moderation can be conveyed well, one of which is through the storytelling method. This KKN activity aims to introduce religious moderation through the storytelling method to students at TPQ Nagari Seulakat Ulakan. The results shows that the program is running and being well received by the students at TPQ Nagari Seulakat Ulakan. The students enjoy listening to every story told by the KKN TEAM, the students have also gradually begun to apply an attitude of religious moderation in their daily lives.